Effects of deep‐fat frying temperature on antioxidant properties of whole wheat doughnuts. (30th October 2017) - Nsabimana, Phénias; Powers, Joseph R.; Chew, Boon; Mattinson, Scott; Baik, Byung‐Kee
Summary: The total phenolic (TP) content, phenolic acid composition and in vitro antioxidant capacity of whole wheat doughnuts fried at 120–180 °C were determined to identify the effects of frying temperature. Significant differences ( P  < 0.05) in TP content were observed between doughnuts fried at different temperatures. The TP content of doughnuts decreased significantly when doughnuts were deep‐fat fried. The TP content of doughnuts increased with elevation with frying temperatures. These increases in TP content of doughnuts were also detected in the determination of individual phenolic compounds using HPLC. DPPH radical and iron‐chelating capacity of deep‐fat fried doughnuts exhibited increases with elevation of frying temperature from 120 to 180 °C. Deep‐fat frying at 120 °C lowered lipid peroxidation inhibition capacity of doughnuts prepared from both refined flour and whole‐grain meals and increased consistently with increased frying temperature from 120 to 180 °C. Moderate deep‐fat frying temperature would increase the content and activity of antioxidants of doughnuts. Abstract : Antioxidant activities of doughnuts by deep‐oil frying temperature.